Revolutionary Robots in Space - Thomas, Rachael L. (Minneapolis : Lerner Publications, 2019)
"What kinds of robots can be found in space, and what do they do? Help readers learn all about how robots are used in outer space with informative, engaging text and stunning photographs straight from space experts."-- Provided by publisher.
t Did a Mars robot find alien evidence? -- t Origami robot accomplice -- t Mission: Martian life -- t
Includes index
Keywords: Space robotics -- Juvenile literature; Robots -- Juvenile literature; Space probes -- Juvenile literature; Juvenile works; Juvenile literature